Online Peers and Delinquency: Distinguishing Influence, Selection, and Receptivity Effects for Offline and Online Peers with Longitudinal Data - McCuddy, Timothy (Journal of developmental and life-course criminology, 2024)
The field of criminology has spent nearly a century investigating the link between peers and delinquency, but only recently turned its attention to the online peer context. We examine three ways online and offline peer delinquency are related to self-reported delinquency. In theory, online peer delinquency may influence delinquent behavior independently of the influence from the physical presence of delinquent peers. Adolescents may also select online peers who are similar to their offline peers, and experiences online may contribute to being more receptive to offline peer influence. We use survey data from a longitudinal sample of middle and high school students in a large, metropolitan area, which includes measures of online peer support for delinquency and perceived delinquency of offline peers. Employing path models, we find that perceiving to have offline delinquent peers is partly related to previous behavior but also to previous experiences with online friends. We also find that the measures of both offline and online peer delinquency are independently related to later self-reported delinquency, and online peer support for violence can enhance the apparent influence of offline violent peers. Overall, this study illustrates that research examining delinquent peer influence should also include online peer processes.